Analiza okoljskih in ekonomskih vplivov mineraliziranega lesa na primeru Plečnikove klopce z uporabo LCA in LCC metodologije - Remic, Katarina (Les (Ljubljana), 2023)
Wood is considered a promising raw material for the circular bioeconomy and has the ability to store biogenic carbon, and this is one reason why we want to extend the service life of wood. Toxic chemicals are often used for wood preservation, but hydroxyapatite seems to be an environmentally friendly solution for wood mineralization. LCA and LCC analyses were performed on a case study of a Plečnik bench, comparing mineralized wood with a service life of 16 and 24 years to a non-mineralized reference variant. LCA was based on EN ISO 14040 and EN ISO 14044, while LCC was adapted from the European Commission’s LCC tool for public procurement. When comparing the results, mineralized wood with a service life of 24 years proved to be the most environmentally friendly and cost-effective option. The mineralized wood with a service life of 16 years had the greatest negative environmental impact, while the most expensive option was the reference wood.
Keywords: analiza življenjskega cikla; environmental impacts; hidroksiapatit; hydroxyapatite; LCA; life cycle assessment; mineralized wood; mineraliziran les; vplivi na okolje